CONTRIBUIÇÃO PARA A IMPLANTAÇÃO DE UM SISTEMA DE INFORMAÇÃO COM BASE NA GESTÃO DO CONHECIMENTO NO PROGRAMA INTERDISCIPLINAR DE GERIATRIA E GERONTOLOGIA DA UNIVERSIDADE FEDERAL FLUMINENSE - Mantovani, Heloisa Helena Rosmaninho (2004)
The present work proposes to contribute for the implantation of a system of information returned to the administration of the knowledge in the Program of Health of the Geriatrics and Gerontology of Rio de Janeiro Federal University PIGG/UFF. For to develop the study a strategic tool, the Diagram of Flow of Data - DFD, was used. In that case study it was made a survey with professionals that work in the program, with the documents used by each one and your relations. It was tried to collaborate with the model of an only handbook for future implantation of the Patient's Electronic Handbook - PEP, seeking to optimize the exchange of information among the team of professionals that work in the Program and, also, a better life quality for the elderly accompanied in the PIGG/UFF.